A new species of Pleroma (Melastomataceae: Melastomateae) endemic to Southern Cadeia do Espinhaço, Minas Gerais, Brazil - Meyer, Fabrício Schmitz; Pacifico, Ricardo; Almeda, Frank (Phytotaxa, 2022)
A new species of Pleroma, endemic to Southern Cadeia do Espinhaço in Minas Gerais, Brazil, is described. Pleroma piranii is morphologically similar to Pleroma velutinum but differs in having larger leaves 2.5 ̶ 7.1 × 1.4 ̶ 4.7 cm (vs. 2.4 ̶ 4.1 × 1.3 ̶ 2.1 cm in P. velutinum), that are densely sericeous on the adaxial surface (vs. moderately strigose), with 7 veins (vs. 5 veins), with obtuse to slightly cordate base (vs. obtuse base only), and completely glabrous style (vs. moderately beset with appressed white eglandular trichomes along much of their length). The distributions of these two species are allopatric; P. piranii occurs only in Minas Gerais, while P. velutinum occurs only in Bahia. According to our assessments based on IUCN criteria, P. piranii is Endangered (EN), because its occurrence is restricted, its populations are small, and most of them occur in unprotected areas. Here we present a description for this new species, taxonomic notes, a distribution map, a chromosome number count, illustration and photos, and a conservation assessment.